“Tourism and work: Investigating the hidden side of tourism in Portuguese tourism films (1910-1980)”, , 12-13 Novembro 2015. - Sampaio, S. (Seminário Internacional ‘O Trabalho no Ecrã: Memórias e Identidades Sociais através do Cinema’, 2015)
The study of tourism has been shaped by the dichotomy of work versus leisure, whereby tourism is normally conceived as an expression of the latter. As a result, most research tends to turn a blind eye to work-related aspects, perceived to be the concern of more business-orientated studies. The emergence, within the social sciences, of tourism as a topic worth investigating only really took off after a shift of focus away from production towards consumption, often in reaction to Marxist-based approaches. Moreover, since the so-called ‘culturalist turn’, the tendency to privilege symbolic and representational processes, in detriment of material ones, has reinforced this divide. Adopting an understanding of tourism that does not follow these tendencies, this paper is concerned with recuperating the ‘hidden side’ of tourism – i.e. work. My analysis draws on research conducted at the National Archive of the Moving Image (ANIM) of the Portuguese Film Museum (Cinemateca Portuguesa – Museu do Cinema), where I have been investigating tourism films produced in Portugal between 1910 and 1980, as part of the exploratory project ‘Behind the Camera: Practices of visuality and mobility in the Portuguese tourism film’ (EXPL/IVC-ANT/1706/2013), financed by Portuguese national funds through FCT/MCTES.